Human Umbilical Cord Mesenchymal Stem Cells-Derived Exosomes Attenuates Experimental Periodontitis in Mice Partly by Delivering miRNAs - Li K; Gu X; Zhu Y; Guan N; Wang J; Wang L (International Journal of Nanomedicine)
Ke Li,1 Xiaoli Gu,1 Yanan Zhu,1 Ning Guan,2 Jinlei Wang,3 Linyuan Wang1 1Department of Periodontics and Mucosa, The second Affiliated Hospital of Jinzhou Medical University, Jinzhou, Liaoning, 121000, People’s Republic of China; 2Key Laboratory of Brain and Spinal Cord Injury Research, First Affiliated Hospital of Jinzhou Medical University, Jinzhou, Liaoning, 121000, People’s Republic of China; 3School of Pharmacy, Jinzhou Medical University, Jinzhou, Liaoning, 121000, People’s Republic of ChinaCorrespondence: Linyuan Wang, Email wangly@jzmu.edu.cnIntroduction: Periodontitis is the most common non-communicable disease in humans. The main challenge in the treatment of periodontitis is to effectively control periodontal inflammation and promote tissue repair. Human umbilical cord mesenchymal stem cells-derived exosomes (hucMSCs-exo) have been reported to modulate inflammatory responses and promote tissue repairment mainly through miRNAs in several diseases. However, the effect of hucMSCs-exo on periodontitis remains unknown. In this study, we hypothesized that hucMSCs-exo could inhibit bone destruction in periodontitis mice.Methods: In this study, we constructed and characterized the exo@H drug delivery platform. Lipopolysaccharide was used to construct an inflammatory microenvironment in vitro to detect MC3T3-E1 cells proliferation and bone regeneration capacity. Ligation induced to construct an experimental periodontitis mouse model. The distance of the cement-enamel junction (CEJ) to the alveolar bone crest (ABC) was measured for bone resorption evaluation. Hematoxylin-eosin (H&E) staining and Tartrate resistant acid phosphatase (TRAP) staining were used to observe periodontal tissue changes. MicroRNA (miRNA) sequencing was used to detect differential genes and for bioinformatics analysis. Real-time quantitative polymerase chain reaction (qRT-PCR). WB assay and dual luciferase assay were used to further validate the screened differentially expressed miRNAs and the targeted binding relationship with the corresponding target genes.Results: We found that lyophilized hucMSCs-exo promoted the proliferation and osteogenic differentiation of MC3T3-E1 cells, and showed more significant proliferative and osteogenic differentiation abilities in combination with the hydrogel (P < 0.05). Using periodontitis mice, bone resorption evaluation revealed a significant reduction in alveolar bone resorption in the exo@H group compared to the hydrogel group (P < 0.01), and exo@H was able to reduce the inflammatory response of periodontal tissues and the number of osteoclasts on the surface of the alveolar bone compared to the hydrogel group. Moreover, 59 miRNAs were upregulated, such as let-7f-5p and miR-203-3p, which positively targeted IL-13 and Nit2, respectively.Discussion: These results suggest that exo@H provides protection against periodontitis partly by delivering miRNAs to periodontal tissue. Our results confirm the feasibility of the exo@H delivery platform we constructed and the effectiveness of its use for periodontitis treatment, and this study provides a promising approach for the treatment of periodontitis via miRNA.Keywords: periodontitis, exosomes, MC3T3-E1, microRNA, gene